HUBUNGAN KARAKTERISTIK IBU DENGAN STATUS GIZI KURANG PADA BALITA DI PUSKESMAS PASAWAHAN KABUPATEN PURWAKARTA 2017 - Widiya, Ika; Yani, Ahmad; Aminarista, Aminarista (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2018)
Background: Nutrition is one of important factors to determine the quality of human resources. Undernourish of the child is disrupted of growth and development,such as protein energy deficiency (PED). The prevalence of underweight children at Pasawahan districh in 2017 is 2,8% from 3669 toddler. Objective: This study aims to know the correlation between mother characteristic and undernourish on toddler at Pusesmas Pasawahan in 2017. Method: This study used observasional research by using cross sectional approach. The sampels of this study were toddler in area of PHC Pasawahan Purwakarta. Sampling used stratifies random sampling method. Data collection using questionnaire and used Chi Square and Fisher’s exact test for analysis. Result: The Study shows that there are no correlation between mother age (p=1,000), mother education background (p=0,409), mother knowledge (p=0,309), number of children (p=0,393), and correlation between family income and undernourish status of toddler (p=0,039). Conclusion: There is no correlation between mother age, mother education background, mother knowledge, and number of undernourish toddler. The correlation between family income and undernourish status of toddler.